A microwave-absorbing and heat-insulating integrated composite material and preparation method thereof

By using silicon carbide nanowire skeleton and nanomagnetic particles to modify it in the absorbing material, the problem of insufficient electromagnetic wave absorption performance in high-temperature environment is solved, and efficient wave absorption and heat insulation effect is achieved. It is suitable for Aerospace field.

CN116396079BActive Publication Date: 2024-12-13CHENGDU AIRCRAFT INDUSTRY GROUP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310303738.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-27
Publication Date
2024-12-13
Estimated Expiration
2043-03-27

AI Technical Summary

Technical Problem

The electromagnetic wave absorption performance of existing wave absorbing materials in high temperature environments is difficult to meet the application needs of the aerospace field, and the surface temperature of the equipment increases due to long-term aerodynamic heating, which affects the wave absorption performance.

Method used

Silicon carbide nanowires are used as the skeleton to modify nanomagnetic particles on the surface, and silicon carbide nanowire aerogel is formed through carbonization treatment and silicon thermal reduction reaction, and metal organic chemical vapor deposition treatment is carried out to form porous structures and multi-stage multiphase magnetic media. Electric composite microstructure, enhance wave absorption and thermal insulation performance.

Benefits of technology

A wave-insulating integrated composite material with excellent wave absorption and heat insulation performance in high temperature environments has achieved a thermal conductivity of less than 0.062W/(mK) at 1000℃, wide-band electromagnetic wave absorption characteristics, and reflectivity is better than -10dB , the effective bandwidth of 90% absorption rate reaches 8.96GHz.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116396079B_ABST
    Figure CN116396079B_ABST
Patent Text Reader

Abstract

The present application discloses an integrated wave-absorbing and heat-insulating composite material and a preparation method thereof, and relates to the technical field of wave-absorbing composite materials; the application aims to solve the technical problem that the electromagnetic wave absorption performance and heat-insulating performance of existing composite materials need to be improved; the integrated wave-absorbing and heat-insulating composite material has silicon carbide nanowires as a skeleton, and the surface is modified with nano-magnetic particle materials; wherein the mass ratio of the silicon carbide nanowires to the nano-magnetic particles is 1:0.5-2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of wave-absorbing composite materials, and in particular to a wave-absorbing and heat-insulating integrated composite material and a preparation method thereof. Background Art

[0002] With the advancement of radar detection technology, the requirements for the wave absorbing performance of equipment in the aerospace field in various environments are becoming higher and higher, such as the electromagnetic wave absorption performance of the wave absorbing materials used to prepare equipment in the aerospace field, and how to avoid the increase in surface temperature of equipment in the aerospace field due to long-term aerodynamic heating during high-speed flight, which affects the wave absorbing performance of the equipment.

[0003] However, the electromagnetic wave absorption performance of existing absorbing materials in high temperature environments is difficult to meet application requirements. Summary of the invention

[0004] The main purpose of the present application is to provide an integrated wave-absorbing and heat-insulating composite material and a preparation method thereof, aiming to solve the technical problem that the electromagnetic wave absorption performance of existing wave-absorbing materials in high-temperature environments is difficult to meet application requirements.

[0005] In order to solve the above technical problems, an embodiment of the present application proposes an integrated wave-absorbing and heat-insulating composite material, which has silicon carbide nanowires as a skeleton and is surface-modified with nanomagnetic particle materials; wherein the mass ratio of the silicon carbide nanowires to the nanomagnetic particles is 1:0.5 to 2.

[0006] As some optional embodiments of the present application, the nanomagnetic particles include at least one of nano Fe, Co, Ni, FeCo, FeNi and CoNi particles.

[0007] As some optional embodiments of the present application, the diameter of the nanomagnetic particles is 8 to 15 nm.

[0008] In order to solve the above technical problems, the embodiment of the present application further proposes: a method for preparing a wave-absorbing and heat-insulating integrated composite material, comprising the following steps:

[0009] The biomass material is vacuum freeze-dried and then carbonized to obtain biomass carbon aerogel;

[0010] Carbothermal reduction reaction is carried out using the biomass carbon aerogel as a precursor and a silicon source to obtain silicon carbide nanowire aerogel;

[0011] The silicon carbide nanowire aerogel is subjected to metal organic chemical vapor deposition treatment to obtain a wave absorbing and heat insulating integrated composite material.

[0012] As some optional embodiments of the present application, the biomass material includes at least one of eggplant, wax gourd, loofah, grapefruit peel, sugar cane and wood.

[0013] As some optional embodiments of the present application, the vacuum freeze-drying temperature is -40°C to -80°C, the drying time is 24h to 48h, and the drying gas pressure is 5Pa to 15Pa.

[0014] As some optional implementation modes of the present application, the carbonization treatment refers to: carrying out the carbonization treatment under the protection of an inert atmosphere, heating the temperature to 750°C to 900°C at a heating rate of 3°C / min and reacting for 1h to 3h.

[0015] As some optional embodiments of the present application, the carbon thermal reduction reaction includes: under the protection of an inert atmosphere, uniformly mixing the silicon source and the biomass carbon aerogel, heating the temperature to 1500° C. at a heating rate of 5° C. / min and keeping the temperature for 2 hours.

[0016] As some optional embodiments of the present application, the mixing mass ratio of the silicon source to the biomass carbon aerogel is 1:1.8-2.4.

[0017] As some optional embodiments of the present application, the silicon source is a mixture of elemental silicon and silicon dioxide, and the mixing mass ratio of the elemental silicon and the silicon dioxide is 4:8.

[0018] As some optional embodiments of the present application, the silicon carbide nanowire aerogel is subjected to metal organic chemical vapor deposition to obtain an integrated wave absorbing and heat insulating composite material, including:

[0019] placing the acetylacetonate metal compound into an upstream region of a dual-temperature tubular furnace, and placing the silicon carbide nanowire aerogel into a downstream region of the dual-temperature tubular furnace;

[0020] After the dual-temperature tubular furnace is evacuated, a reducing atmosphere of hydrogen is introduced, and after 6 cycles, the temperature is increased, the upstream area is heated to 100-300° C., the downstream area is heated to 500-700° C., and the reaction is kept at this temperature for 2 hours;

[0021] After the reaction is completed, the mixture is cooled to room temperature under the protection of hydrogen to obtain a microwave-absorbing and heat-insulating integrated composite material.

[0022] As some optional implementation modes of the present application, the heating rate of the upstream region is 2°C / min, and the heating rate of the downstream region is 5°C / min.

[0023] As some optional embodiments of the present application, the mass ratio of the acetylacetonate metal compound to the silicon carbide nanowire aerogel is 15:5.

[0024] As some optional embodiments of the present application, the acetylacetonate metal compound includes at least one of acetylacetonate nickel, acetylacetonate iron and acetylacetonate cobalt.

[0025] Compared with the prior art, the embodiment of the present application proposes an integrated wave-absorbing and heat-insulating composite material, wherein the composite material is based on silicon carbide nanowires as a skeleton and the surface is modified with nanomagnetic particle materials; wherein the mass ratio of the silicon carbide nanowires to the nanomagnetic particles is 1:0.5-2; wherein the silicon carbide nanowires overlap each other to form a micron-level porous structure, effectively inhibiting heat conduction and forming a good high-temperature heat-insulating effect, and the thermal conductivity at 1000°C is less than or equal to 0.062W / (mK); the conductive magnetic nanoparticles are modified on the surface of the silicon carbide nanowires to form a multi-level multi-phase magneto-dielectric composite microstructure, which has significant dielectric polarization relaxation, magnetic loss and multiple electromagnetic scattering effects, so that the light, strong and broadband electromagnetic wave absorption characteristics are obtained, and the effective bandwidth with a reflectivity better than -10dB (90% absorption rate) reaches 8.96GHz, and the corresponding strongest absorption peak reaches -47.75dB. Based on this, the integrated wave-absorbing and heat-insulating composite material described in the embodiment of the present application has both excellent wave-absorbing performance and heat-insulating performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a microscopic morphology of the integrated wave-absorbing and heat-insulating composite material obtained in Example 1 of the present application;

[0027] Figure 2 It is the electromagnetic parameter diagram of the integrated wave-absorbing and heat-insulating composite material obtained in Example 1 of the present application in the frequency band of 2 to 18 GHz; wherein, Figure 2 a is the real part curve of complex dielectric constant, Figure 2 b is the curve of the imaginary part of the complex dielectric constant, Figure 2 c is the real part curve of complex magnetic permeability, Figure 2 d is the curve of the imaginary part of complex magnetic permeability;

[0028] Figure 3 This is a graph of the wave absorption performance of the integrated wave absorbing and heat insulating composite materials of different thicknesses obtained in Example 1 of the present application in the frequency range of 2 to 18 GHz. DETAILED DESCRIPTION

[0029] It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0030] With the advancement of radar detection technology, the requirements for the wave absorbing performance of equipment in the aerospace field in various environments are becoming higher and higher, such as the electromagnetic wave absorption performance of the wave absorbing materials used to prepare equipment in the aerospace field, and how to avoid the increase in surface temperature of equipment in the aerospace field due to long-term aerodynamic heating during high-speed flight, which affects the wave absorbing performance of the equipment.

[0031] However, the electromagnetic wave absorption performance of existing absorbing materials in high temperature environments cannot meet the application requirements. For example, SiC aerogel has a three-dimensional nano-graded porous network structure, which has high specific surface area, high porosity, low density and extremely low thermal conductivity coefficient. It is a promising integrated composite material for absorbing and heat-insulating. However, SiC aerogel still has problems such as poor mechanical properties, weak dielectric loss and no magnetic loss mechanism, which is not conducive to obtaining good electromagnetic wave absorption performance.

[0032] The main purpose of this application is to provide an integrated wave-absorbing and heat-insulating composite material and a preparation method thereof, aiming to solve the technical problem that the electromagnetic wave absorption performance of existing wave-absorbing materials in high-temperature environments is difficult to meet application requirements.

[0033] In order to solve the above technical problems, the embodiments of the present application propose an integrated wave-absorbing and heat-insulating composite material, which has a silicon carbide nanowire as a skeleton and is modified with nanomagnetic particle materials on the surface; wherein the mass ratio of the silicon carbide nanowire to the nanomagnetic particles is 1:0.5-2. As some optional embodiments of the present application, the nanomagnetic particles include at least one of nano Fe, Co, Ni, FeCo, FeNi and CoNi particles. As some optional embodiments of the present application, the diameter of the nanomagnetic particles is 8-15nm.

[0034] Compared with the prior art, the embodiment of the present application proposes an integrated wave-absorbing and heat-insulating composite material, wherein the integrated wave-absorbing and heat-insulating composite material uses silicon carbide nanowires as a skeleton, and the silicon carbide nanowires overlap each other to form a micron-level porous structure, which can effectively inhibit heat conduction and form a good high-temperature heat-insulating effect, and its thermal conductivity at 1000°C is less than or equal to 0.062W / (mK); the integrated wave-absorbing and heat-insulating composite material of the present application also uses nanomagnetic particle materials in the silicon carbide nanowire skeleton to form a multi-level multi-phase magneto-dielectric composite microstructure, which has significant dielectric polarization relaxation, magnetic loss and multiple electromagnetic scattering effects, so that the light, strong and broadband electromagnetic wave absorption characteristics are obtained, and the effective bandwidth with a reflectivity better than -10dB (90% absorption rate) reaches 8.96GHz, and the corresponding strongest absorption peak reaches -47.75dB. Based on this, the integrated wave-absorbing and heat-insulating composite material of the embodiment of the present application uses silicon carbide nanowires with heat-insulating properties as a skeleton to ensure that the integrated wave-absorbing and heat-insulating composite material still has good electromagnetic wave absorption performance in a high temperature environment.

[0035] In order to solve the above technical problems, the embodiment of the present application further proposes: a method for preparing a wave-absorbing and heat-insulating integrated composite material, comprising the following steps:

[0036] Step S1, vacuum freeze-drying the biomass material and then carbonizing it to obtain biomass carbon aerogel.

[0037] In specific applications, in order to obtain biomass carbon aerogel with better performance, the following definition is made: the biomass material includes at least one of eggplant, wax gourd, loofah, grapefruit peel, sugarcane and wood. In some embodiments of the present application, the vacuum freeze-drying temperature is -40°C to -80°C, the drying time is 24h to 48h, and the drying pressure is 5Pa to 15Pa; preferably, the vacuum freeze-drying temperature is -60°C, the drying time is 48h, and the drying pressure is 10Pa. In some embodiments of the present application, the carbonization treatment refers to: under the protection of an inert atmosphere, the temperature is increased to 750°C to 900°C at a heating rate of 3°C / min for 1h to 3h; preferably, the carbonization treatment is carried out under nitrogen protection, the carbonization temperature is 800°C, and the carbonization time is 2h.

[0038] In specific applications, the biocarbon aerogel has poor stability and strict requirements on the preparation process. During the carbonization process, if there is water evaporation or the heating rate is too fast, it is not conducive to the formation of a porous structure. Therefore, before the carbonization treatment, it is necessary to first perform a dehydration treatment and then prepare it under the condition of controlling the heating rate.

[0039] Step S2: using the biomass carbon aerogel as a precursor and a silicon source to carry out a carbothermal reduction reaction to obtain silicon carbide nanowire aerogel.

[0040] In specific applications, in order to obtain silicon carbide nanowire aerogel with better performance, the following definition is made: the carbon thermal reduction reaction includes: under the protection of an inert atmosphere, the silicon source and the biomass carbon aerogel are uniformly mixed, and then the temperature is increased to 1500°C at a heating rate of 5°C / min for 2 hours of insulation reaction. In some embodiments of the present application, the mixing mass ratio of the silicon source to the biomass carbon aerogel is 1:1.8-2.4. In some embodiments of the present application, the silicon source is a mixture of elemental silicon and silicon dioxide, and the mixing mass ratio of the elemental silicon and the silicon dioxide is 4:8. Through the above definition, the yield can be increased, which is more conducive to the generation of silicon carbide.

[0041] Step S3: subjecting the silicon carbide nanowire aerogel to metal organic chemical vapor deposition to obtain a microwave absorbing and heat insulating integrated composite material.

[0042] In specific applications, in order to obtain an integrated wave-absorbing and heat-insulating composite material with better performance, the following restrictions are made: the silicon carbide nanowire aerogel is subjected to metal organic chemical vapor deposition treatment to obtain an integrated wave-absorbing and heat-insulating composite material, including: placing an acetylacetone metal compound into the upstream area of ​​a dual-temperature tubular furnace, and placing the silicon carbide nanowire aerogel into the downstream area of ​​the dual-temperature tubular furnace; evacuating the dual-temperature tubular furnace and then introducing a reducing atmosphere of hydrogen, and after circulating 3-6 times, heating the upstream area to 100-300°C, preferably, heating the upstream area to 200°C-250°C; heating the downstream area to 500-700°C, preferably, heating the downstream area to 600°C-700°C; keeping the reaction warm for 2 hours; after the reaction is completed, cooling to room temperature under hydrogen protection to obtain an integrated wave-absorbing and heat-insulating composite material. The present application achieves the purpose of controlling the volatilization rate of the metal compound (acetylacetonate metal compound) and enabling it to reach the deposition zone in the downstream zone by limiting the temperature in the upstream zone; at the same time, by limiting the temperature in the downstream zone, the metal compound (acetylacetonate metal compound) is fully reacted in the deposition zone and deposited on silicon carbide.

[0043] In a specific application, in order to obtain a composite material with better wave absorption and thermal insulation performance, the heating rate of the upstream region is 2°C / min, and the heating rate of the downstream region is 5°C / min. In some embodiments of the present application, the mass ratio of the acetylacetonate metal compound to the silicon carbide nanowire aerogel is 15:5. In some embodiments of the present application, the acetylacetonate metal compound includes at least one of nickel acetylacetonate, iron acetylacetonate, and cobalt acetylacetonate.

[0044] The integrated wave-absorbing and heat-insulating composite material prepared by the above-mentioned preparation method has silicon carbide nanowires as the skeleton, and the surface is modified with nanomagnetic particle materials; wherein the mass ratio of the silicon carbide nanowires to the nanomagnetic particles is 1:0.5-2; wherein the silicon carbide nanowires overlap each other to form a micron-level porous structure, effectively inhibiting heat conduction and forming a good high-temperature heat insulation effect, and the thermal conductivity at 1000°C is less than or equal to 0.062W / (mK); the conductive magnetic nanoparticles are modified on the surface of the silicon carbide nanowires to form a multi-level multi-phase magneto-dielectric composite microstructure, which has significant dielectric polarization relaxation, magnetic loss and multiple electromagnetic scattering effects, so that the light, strong and broadband electromagnetic wave absorption characteristics are obtained, and the effective bandwidth with a reflectivity better than -10dB (90% absorption rate) reaches 8.96GHz, and the corresponding strongest absorption peak reaches -47.75dB. Based on this, the integrated wave-absorbing and heat-insulating composite material described in the embodiment of the present application has both excellent wave absorption performance and heat insulation performance.

[0045] The integrated wave-absorbing and heat-insulating composite material and its preparation method described in this application are described in detail below in conjunction with specific embodiments:

[0046] Example 1

[0047] (1) Preparation of biomass carbon aerogel: Peel the fresh eggplant purchased, weigh 20g and put it into a vacuum freeze drying oven, and freeze-dry the peeled eggplant at a pressure of 10Pa and a temperature of -60°C for 30h. Put the freeze-dried eggplant into a tubular furnace, first evacuate the tubular furnace and then introduce inert gas nitrogen, cycle 3 times to ensure that there is no oxygen in the glass tube, then heat the facility at a rate of 3°C / min, heat to 800°C and keep warm for 2h, and finally cool naturally to room temperature under nitrogen to obtain biomass carbon aerogel.

[0048] (2) Preparation of silicon carbide nanowire aerogel: First, 5g of biomass carbon aerogel obtained in step (1) was uniformly mixed with 12g of silicon source material, wherein the silicon source material consisted of 4g of elemental silicon and 8g of silicon dioxide. The porous carbon and silicon source mixture was placed in a tubular furnace, and the tubular furnace was evacuated and then introduced with inert gas argon. After three cycles, the tubular furnace was set to heat up at a rate of 5°C / min and kept at 1500°C for 2h. After natural cooling, silicon carbide nanowire aerogel was obtained.

[0049] (3) Preparation of integrated wave-absorbing and heat-insulating composite materials: Weigh 15g of nickel acetylacetonate and place it in the upstream area of ​​a dual-temperature tubular furnace, and weigh 5g of silicon carbide nanowire aerogel and place it in the downstream area of ​​the dual-temperature tubular furnace. First, evacuate the tubular furnace and then introduce reducing atmosphere hydrogen. After 6 cycles, set the heating rate of the upstream area to 2℃ / min and the maximum temperature to 200℃. Set the heating rate of the downstream area to 5℃ / min and the maximum temperature to 700℃. After reaching the maximum temperature, react for 2h; cool naturally to room temperature under hydrogen protection to obtain the microscopic morphology as shown in the figure. Figure 1 The integrated microwave-absorbing and heat-insulating composite material shown.

[0050] The thermal diffusion coefficient of the composite material in the thickness direction was tested using a laser thermal conductivity meter of model Netzsch LFA 427. The heat capacity of the material was obtained by testing with a synchronous thermal analyzer Setsys Evo. The final calculated thermal conductivity of the material at 1000°C was 0.058W / (mK).

[0051] The electromagnetic parameters (complex dielectric constant and complex magnetic permeability) of the integrated wave-absorbing and heat-insulating composite material prepared in Example 1 of the present application were tested using an Agilent model N5230A vector network analyzer. The test results are as follows: Figure 2 As shown, Figure 2 a is the real part curve of complex dielectric constant, Figure 2 b is the curve of the imaginary part of the complex dielectric constant, Figure 2 c is the real part curve of complex magnetic permeability, Figure 2 d is the imaginary part curve of complex magnetic permeability. Figure 2It can be seen that the integrated wave-absorbing and heat-insulating composite material obtained in this embodiment has a moderate complex dielectric constant and a high complex magnetic permeability, indicating that it has both strong dielectric loss and strong magnetic loss capabilities and can obtain good impedance matching characteristics.

[0052] According to the transmission line theory, based on the electromagnetic parameters tested, the wave absorption performance diagram of the wave absorption and heat insulation integrated composite material with different thicknesses prepared in Example 1 was obtained, as shown in FIG. Figure 3 As shown, it can be seen that as the material thickness increases, the absorption peak moves to low frequency; when the material thickness is 1.4mm, it is better than -10dB (90% absorption rate), the bandwidth is 7.2GHz, and the corresponding absorption peak reaches -21.75dB (more than 99% absorption).

[0053] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A microwave-absorbing and heat-insulating integrated composite material, characterized in that: The integrated wave-absorbing and heat-insulating composite material is prepared by the following steps: (1) Preparation of biomass carbon aerogel: Peel the fresh eggplant purchased, weigh 20g and put it into a vacuum freeze drying oven, and freeze-dry the peeled eggplant at a pressure of 10Pa and a temperature of −60℃ for 30h; put the freeze-dried eggplant into a tubular furnace, first evacuate the tubular furnace and then introduce inert gas nitrogen, and cycle it 3 times to ensure that there is no oxygen in the glass tube, then heat the facility at a rate of 3℃ / min, heat it to 800℃ and keep it warm for 2h, and finally cool it naturally to room temperature under nitrogen to obtain biomass carbon aerogel; (2) Preparation of silicon carbide nanowire aerogel: First, 5 g of the biomass carbon aerogel obtained in step (1) was uniformly mixed with 12 g of a silicon source material, wherein the silicon source material consisted of 4 g of elemental silicon and 8 g of silicon dioxide; the porous carbon and silicon source mixture was placed in a tubular furnace, and the tubular furnace was evacuated and then introduced with inert gas argon. After three cycles, the tubular furnace was set to heat up at a rate of 5 °C / min and kept at 1500 °C for 2 h; after natural cooling, silicon carbide nanowire aerogel was obtained; (3) Preparation of integrated wave-absorbing and heat-insulating composite materials; 15 g of nickel acetylacetonate was weighed and placed in the upstream area of ​​a dual-temperature tubular furnace, and 5 g of silicon carbide nanowire aerogel was weighed and placed in the downstream area of ​​the dual-temperature tubular furnace; the tubular furnace was first evacuated and then a reducing atmosphere of hydrogen was introduced. After six cycles, the heating rate of the upstream area was set to 2 °C / min and the maximum temperature was set to 200 °C; the heating rate of the downstream area was set to 5 °C / min and the maximum temperature was set to 700 °C. After reaching the maximum temperature, the reaction was allowed to proceed for 2 h; the furnace was naturally cooled to room temperature under the protection of hydrogen.

Citation Information

Cited By

  • Preparation method of FeCo (SiO2 / C) film and wave-absorbing, heat-insulating and anti-corrosion application of FeCo (SiO2 / C) film

    CN120591959A